THE DISTRIBUTION OF MACARANGA, GENUS (FAMILY EUPHORBIACEAE) IN PENANG ISLAND, PENINSULAR MALAYSIA - Rahmad Zakaria; Nik Fadzly Nik Rosely; Mashhor Mansor; Mohd Yunus Zakaria (Tropical Life Sciences Research, 2008)
A total of eight species of Macaranga are identified in this study, which were carried out from March to December 2005 in Penang Island. The most common species recorded is Macaranga tanarius which is found in almost every disturbed habitats, except for primary forested area. Unlike M. tanarius, M. javanica (the second most common species) are also well distributed except in highly populated human inhabitation areas. The other six species are scattered without any clear distributing pattern. Land clearings by human activities are likely the main cause that triggers the spread of M. tanarius and M. javanica populations, thus the species are widely distributed and thrive well in these study areas. Sejumlah lapan spesies Macaranga telah dikenal pasti dalam kajian yang dilakukan dari bulan Mac sehingga Disember 2005. Spesies yang paling biasa direkod adalah Macaranga tanarius, ditemui di semua habitat terganggu kecuali di dalam hutan primer. Tidak seperti M. tanarius, spesies kedua tersebar luas, iaitu M. javanica juga dapat ditemui di semua jenis habitat, kecuali di kawasan yang berpenduduk padat. Taburan enam spesies lain tidak menunjukkan pola yang jelas. Pembukaan hutan adalah faktor utama yang dijangkakan merangsang pertumbuhan populasi M. tanarius dan M. javanica, maka tidak hairanlah ia tersebar dengan luas dan berjaya di kebanyakan kawasan kajian berbanding spesies lain.